Experimental Setup and Analysis of Data Logging Software Specifications - Kanniga , E.; Varma, Akhil (International Journal of Psychosocial Rehabilitation, 2019)
Repeated jobs are done fast in batch systems without user interaction. The proposed work doesn’t need special hardware and system support to input data in batch systems. Best for large organizations but small organizations can also benefit from it. It generally has lower capital costs. It has the flexibility to produce a variety of different product variations, or different products. It works well when small production runs are needed